The role of preventive medical examinations in obligatory clinical check-ups of children in Azerbaijan - Z. M. Mustafayeva (LLC "Diagnostics and Vaccines", 2021)
In 2014, obligatory medical check-ups of the child population were legislatively introduced in Azerbaijan. At the same time, for the early detection of diseases and various pathological conditions, health services of the country paid special attention to precisely preventive measures which will predetermine both the state of child health, as well as the quality of their life in the future.In order to increase the efficiency of obligatory medical check-ups, the morbidity rates of the child population of Azerbaijan were analyzed based on the results of preventive medical examinations for the period 2014-2019.